Complementary power generation of double linear switched reluctance generators for wave power exploitation. (March 2019) - Pan, J.F.; Li, Qianlong; Wu, Xiaoyu; Cheung, Norbert; Qiu, Li
Highlights: This paper investigates two identical ABLSRGs for wave power generation. The voltage complimentary scheme is proposed. Performance comparison between the proposed method and the independent control is carried out. Abstract: The wave power generation system based on the single linear generator scheme has low energy output and week robustness, especially in low speed conditions and parameter variations. To overcome the problem, a scheme of complementary power compensation generation for two asymmetric bilateral linear switched reluctance generators (ABLSRGs) is proposed in this paper. Mathematic model is first derived and machine characteristics are investigated by the finite element method. The compensation scheme is carefully investigated together with the independent control method. Under the conditions of parameter and velocity variations, experimentation demonstrates that both the voltage control accuracy and system robustness can be guaranteed with the proposed complementary power generation control scheme. Experiment results show that a voltage control precision of 11.75–12.23 V can be obtained, with the voltage reference of 12 V.